'I Have Made a Highway of Biainili': Transportation and Road Networks in the Territories of the Urartian Kingdom - ÇİFÇİ, ALİ (De Gruyter Open Ltd, 2021)
After emerging in the Lake Van Basin of Turkey, the Urartian kingdom expanded its territory across Eastern Anatolia, Northwestern Iran, and Armenia between the late 9th and early 7th century BC. The high altitude of these regions and the climatic conditions, especially long and harsh winters with heavy snowfall, likely forced the Urartian monarchy to establish a reliable network of communication: new roads and new settlements along these roads were established between the capital city Tušpa and other parts of its territory. This study presents a reassessment of the archaeological and textual evidence on Urartian routes used for military campaigns, settlements located along these routes, ancient road remains and means of transportation. © 2021 Walter de Gruyter GmbH, Berlin/Boston.
Keywords: Ancient Roads; Road Network; Transportation; Urartian Kingdom